2018
DOI: 10.1159/000494239
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Fluoride and SO2 Induce DNA Damage and Morphological Alterations in Male Rat Kidney

Abstract: Background/Aims: We investigated the combined toxic effect of sodium fluoride (NaF) and sulfur dioxide (SO2) on kidney morphological changes and DNA damage in male Wistar rats. Methods: In this study we selected totally 96 male Wistar rats (12-week-old) then randomly group-housed them into four cages, treated with deionized water, NaF, SO2 and co-treatment of NaF and SO2 respectively. Morphological changes of kidney were detected by hematoxylin and eosin (H&E) staining at 2, 4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 38 publications
(46 reference statements)
1
3
0
Order By: Relevance
“…Recently it has been shown that co-exposures with fluoride with sulfur dioxide worsen on brain and kidney toxicity [73, 74]. In this study, similar alterations in spermatozoa quality, mitochondrial impaired function, apoptosis increasing have previously evidenced in the fluoride and diabetes exposure at reproductive level; however, their combination aggravates the spermatozoa function.…”
Section: Discussionsupporting
confidence: 78%
“…Recently it has been shown that co-exposures with fluoride with sulfur dioxide worsen on brain and kidney toxicity [73, 74]. In this study, similar alterations in spermatozoa quality, mitochondrial impaired function, apoptosis increasing have previously evidenced in the fluoride and diabetes exposure at reproductive level; however, their combination aggravates the spermatozoa function.…”
Section: Discussionsupporting
confidence: 78%
“…As the primary organ that eliminates wastes from the body, the kidney is particularly susceptible to the effects of environmental toxins [40]. For example, previous animal studies suggested that inhaling of SO 2 can lead to renal tissue lesions, induce oxidative stress responses, and cause dose-dependent increases in DNA injuries in kidney [40][41][42]. In addition to inflammation responses, one study found that O 3 inhalation can modify the gene expression in rat's kidney, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…A large amount of fluoride deposition mainly damages to bones, teeth, and central nervous system via passing through the blood-brain barrier that can lead to insomnia or somnolence and other symptoms ( 12 ). There is evidence that excessive fluoride intake can damage various organs including brain ( 13 , 14 ), liver ( 15 , 16 ), kidney ( 17 ), ovary ( 18 ). Fluoride in the environment into the body is mainly absorbed by the stomach and intestines, through the cell membrane, deposited in bone and soft tissue, causing damage to bone and soft tissue.…”
Section: Introductionmentioning
confidence: 99%